Mammal diversity survey of Ko Pha-ngan in Surat Thani Province, Thailand - Dawn R. Cook-Price; Olga N. Petko; Sunchai Makchai; Taksin Artchawakom; Pongthep Suwanwaree (ZooKeys)
This study aims to survey mammal diversity on Ko Pha-ngan, located 80 km off the east peninsular coast of Surat Thani province, Thailand. Thirteen camera trap sites, 32 transects, six drift line fence traps, five mist net trap sites, and nine live trap sites placed in human settlement, human-disturbed forest, and national park forest from February 2021 to September 2023 were utilized. A total of 28 mammal species of eight orders, 17 families, and 21 genera were found. Among them, 11 species are flying mammals while the remaining are terrestrial. Of the species detected, Manis javanica (pangolin) is critically endangered, while Nycticebus coucang (slow loris monkey) is endange by IUCN Red List. Additionally, Rusa unicolor (sambar deer) is vulnerable and Pteropus cf. hypomelanus (island flying fox), Trachypithecus obscurus (dusky leaf monkey), and Ratufa bicolor (giant black squirrel) are near threatened. These findings highlight the need to conserve and protect both national park forest and human-disturbed forest from anthropogenic pressures due to the finite area of an island, in which potential local extinction risk is higher.